Considerations on the mechanisms of integration of the dead in the early sedentary societies of the Near East (Natufian, 15-11.6 ka cal BP) - Fanny Bocquentin; Camille Noûs (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
With the beginning of sedentary life in the Near East, the practice of burying the dead, which was exceptional throughout the Palaeolithic period, became widespread. From then on, an enduring relationship became established between the living and the dead coexisting in the same settlement, and it seems that the boundary that separated them began to blur. As many burials were excavated long ago, the spatial and stratigraphic evidence and the treatment of corpses are often imprecise. However, there are still indications that a dynamic of interdependence between the living and the dead became more marked over time. We show that, well beyond their passive occupation of the territory of which they are presumed to have been the guardians, the dead took on a decisive role in the foundation and the subsequent restructuring of settlements. The location of the graves and the succession of activities and constructions are evidence of deliberate planning of the dwelling space, in which the role of each actor became sustained over time. The alternation of individual and collective treatments of the deceased seems to correspond to changes in the occupation of each settlement. It can then be seen that if the relationship between graves and dwellings is loosened, the funerary time span lengthens and the boundary between the living and the dead becomes permeable.